2007
DOI: 10.1016/j.entcs.2006.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Automated Fault Localization for C Programs

Abstract: If a program does not fulfill a given specification, a model checker delivers a counterexample, a run which demonstrates the wrong behavior. Even with a counterexample, locating the actual fault in the source code is often a difficult task for the verification engineer. We present an automatic approach for fault localization in C programs. The method is based on model checking and reports only components that can be changed such that the difference between actual and intended behavior of the example is removed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 26 publications
(30 reference statements)
0
41
0
Order By: Relevance
“…For each component correction logic is inserted in the CDFG as described in [9]. That is, each right-hand side of an expression and all control predicates can be replaced by a non-deterministic value.…”
Section: Correction-based Debuggingmentioning
confidence: 99%
See 1 more Smart Citation
“…For each component correction logic is inserted in the CDFG as described in [9]. That is, each right-hand side of an expression and all control predicates can be replaced by a non-deterministic value.…”
Section: Correction-based Debuggingmentioning
confidence: 99%
“…SAT-based debugging [17] partially automates the debugging by finding possible fault locations, i.e., components that can fix the faulty behavior. The usability for complex models was shown for debugging hardware [17] as well as software [9].…”
Section: Introductionmentioning
confidence: 99%
“…What do commonly exist, though, are extensive unit test suites, in particular in the context of modern test-driven design approaches. Griesmayer et al have shown that their technique can (in principle) be extended to work with (failing) test cases, but the published results [23] are prohibitively slow, typically executing in hundreds to thousands of seconds per each small benchmark program. Griesmayer et al have improved the original implementation [24] but only achieve times typically in the hundreds of seconds.…”
Section: Introductionmentioning
confidence: 99%
“…the identification of program locations that can cause erroneous state transitions that eventually lead to observed program failures, is a critical component of the debugging cycle. Since it puts a significant time [47,50] and expertise burden [1,66] on programmers, a variety of different automated fault localisation methods have been proposed [12,14,23,25,26,34,55,56,58]. We describe a fast model-based fault localisation algorithm that, given a test suite, uses symbolic execution methods to fully automatically identify a small subset of program locations within which (under a single-fault assumption) a genuine program repair exists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation